Metal-nonmetal composite coating and method for producing and using same
Patent Information
- Application Number
- CN202611098534.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-20
AI Technical Summary
但是纳米多层/超晶格涂层获得最佳硬度和韧性的沉积条件和工艺窗口非常苛刻,相邻两层纳米层的厚度(调制周期)达到临界值时涂层硬度突然提高甚至2-3倍,但在临界值附近涂层性能急剧下降(Surface&Coatings Technology 519 (2026)132957、Surface&Coatings Technology 365 (2019) 65-69);而纳米层和界面特性受涂层制备工艺影响较大
(1)本发明提供一种金属-非金属复合涂层,所述金属-非金属复合涂层具有层叠的多层结构,其硬度与韧性不随金属层的厚度或层数的增加而产生明显下降,可在较高的金属层厚度或层数仍维持较高的硬度和韧性水平,大大扩展纳米多层/超晶格涂层的工艺窗口。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of materials technology, and in particular to a metal-nonmetal composite coating, its preparation method, and its application. Background Technology
[0002] Nanoscale multilayer coatings refer to multilayer thin films formed by alternating deposition of two or more materials with different compositions or structures at the nanoscale along the coating growth direction. When the coherent growth and periodic repeatability of the nanolayers are strictly controlled, the nanoscale multilayer coating exhibits a superlattice structure. The regular long periodicity of the superlattice structure provides an effective model for nanoscale multilayer research. However, the deposition conditions and process windows for obtaining optimal hardness and toughness in nanoscale multilayer / superlattice coatings are very demanding. When the thickness (modulation period) of two adjacent nanolayers reaches a critical value, the coating hardness suddenly increases by 2-3 times, but the coating performance drops sharply near the critical value (Surface & Coatings Technology 519 (2026) 132957, Surface & Coatings Technology 365 (2019) 65-69). Furthermore, the nanolayer and interface properties are greatly affected by the coating preparation process. Therefore, it is difficult to achieve ideal reinforcement conditions in industrial production, affecting the performance and application of nanoscale multilayer / superlattice coatings.
[0003] If the limitations of the optimal modulation cycle and deposition process can be overcome, the process window for nano-multilayer / superlattice coatings can be greatly expanded, and more types of materials and deposition processes can be used to develop ultra-hard and ultra-tough nano-multilayer coatings. Summary of the Invention
[0004] This invention aims to at least solve one of the aforementioned technical problems existing in the prior art. Therefore, one objective of this invention is to provide a metal-nonmetal composite coating having a multilayered structure, whose hardness and toughness do not significantly decrease with increasing metal layer thickness or number of layers, maintaining high hardness and toughness levels even at higher metal layer thicknesses or numbers, greatly expanding the process window for nano-multilayer / superlattice coatings. A second objective of this invention is to provide a method for preparing the metal-nonmetal composite coating described in the first aspect. A third objective of this invention is to provide an application of the metal-nonmetal composite coating described in the first aspect.
[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A first aspect of the present invention is to provide a metal-nonmetal composite coating comprising alternating layers of Me1X and Me2. Me1 and Me2 are each independently selected from at least one of Ti, Al, Cr, Zr, Hf, W, Mo, Ta, Sc, Ni, and V; Me1X is a boride, carbide, nitride, or oxide of metallic Me1; At least a portion of the metal Me2 in the Me2 layer forms Me2X with X in the Me1X layer; The number of layers in both the Me1X layer and the Me2 layer is greater than or equal to 3.
[0006] In some preferred embodiments, the Me1X layer in the metal-nonmetal composite coating comprises TiB2, and the Me2 layer comprises W.
[0007] In some preferred embodiments, the Me1X layer in the metal-nonmetal composite coating comprises TiAlN, and the Me2 layer comprises Mo.
[0008] In recent years, TiB2 has become a key research focus in the field of next-generation high-performance ceramic materials due to its high hardness, excellent wear resistance, high-temperature stability, and chemical inertness with non-ferrous metals such as aluminum alloys. Because TiB2 coatings have extremely low chemical affinity for non-ferrous metals, adhesion is less likely to occur when machining soft metals such as titanium alloys and aluminum alloys, effectively suppressing built-up edge and cold welding phenomena. Its excellent performance can be attributed to the chemical inertness of TiB2 and the self-lubricating effect of B2O3 generated during the cutting process. Furthermore, the high hardness of the TiB2 coating significantly improves the wear resistance of the tool surface. However, TiB2 has two drawbacks: excessively high intrinsic residual stress and insufficient high-temperature oxidation resistance. To compensate for these shortcomings, a TiB2 / W multilayer coating structure design is adopted. The introduced metal (W) intercalation layer can block the continuous growth of TiB2 columnar crystals, alleviate the accumulation of growth stress, and hinder crack propagation through the multilayer interface effect. However, as mentioned in the background section, the process window for TiB2 / W multilayer coatings is relatively small. With increasing W layer thickness, the coating's hardness and toughness decrease significantly, making it difficult to achieve ideal enhancement conditions. Studies have shown that irradiating low-energy recoil atoms with heavy metal ions (such as W) can replace the traditional thermally driven adsorption atom surface mobility, enabling energy-efficient PVD deposition. By generating high-flux, high-energy W ions, an ion implantation effect can be induced to strengthen the interface, improve film-substrate adhesion, and enhance coating density. If the deposition process of TiB2 / W multilayer coatings can be enhanced by W ion energy-assisted deposition to improve film-substrate adhesion and coating density, it is possible to maintain the coating's high hardness and increase its industrial application value.
[0009] Similarly, bombarding TiAlN with heavy metal (Mo) to increase the energy of ions incident on the substrate during TiAlN preparation aids in the deposition of TiAlN / MoN coatings. This improves the surface atomic mobility, increases coating density, eliminates porosity and microcracks, refines grains, inhibits columnar crystal growth, and enhances the interfacial bonding between the coating and the substrate. Furthermore, the introduction of the MoN phase can further endow the coating with self-lubricating or low-friction properties, optimizing overall mechanical properties.
[0010] There are two main methods for assisted deposition to enhance W ion energy. One is to introduce a high bias voltage to achieve high bias bombardment of W ions, but this will also deposit a high-stress TiB2 coating. The other is to manually adjust the bias voltage of different monolayers, or to configure a system that can automatically run the deposition process. Since the deposition thickness of TiB2 layer and W layer is different, it will increase the factors that need to be adjusted, such as the sputtering time of each target, the spatial layout inside the furnace cavity, and the placement of the workpiece.
[0011] To overcome the shortcomings of the above methods, this invention proposes using bipolar high-power pulsed magnetron sputtering (BP-HiPIMS) to enhance the energy-assisted deposition of W or Mo metal ions to form TiB2 / W or TiAlN / MoN nanolayered coatings. A schematic diagram illustrating the principle of selectively accelerating incident ions using BP-HiPIMS technology is attached. Figure 1 BP-HiPIMS technology involves discharging onto two targets, which act as each other's positive and negative electrodes. One target undergoes glow discharge during the negative pulse application time, while the other target bombards and deposits onto the substrate during the positive pulse application time. A reversal voltage deflects positive ions from the target, allowing the ions to gain energy from the reversal voltage in addition to their initial kinetic energy and bias acceleration, achieving a synergistic effect of glow discharge and bombardment. This invention utilizes a BP-HiPIMS power supply to selectively and effectively accelerate heavy metal ions by staggering the discharge pulse times, enhancing their energy reaching the substrate. High-energy heavy metal ion bombardment forms a dense metal layer, maintaining the coating's mechanical properties. Simultaneously, high-energy heavy metal ions enhance surface atomic mobility, promoting the diffusion bonding of free non-metallic atoms at the interface. Sufficiently energetic heavy metal ions trigger the re-sputtering of lightweight non-metallic atoms, causing them to migrate into the metal layer and form a partial metal-non-metal phase, thus maintaining a high level of hardness in the BP-HiPIMS-prepared coating. The present invention can also control the energy of different ions incident on the substrate by adjusting the glow time and magnitude of the reverse voltage of BP-HiPIMS, so as to meet the preparation of different coatings.
[0012] In some preferred embodiments, the thickness d1 of the Me1X layer satisfies 0 <d1≤100nm。
[0013] In some preferred embodiments, the thickness d2 of the Me2 layer satisfies 0 <d2≤100nm。
[0014] In some preferred embodiments, the thickness of the metal-nonmetal composite coating is 0.5~10μm.
[0015] The second aspect of the present invention is to provide a method for preparing the metal-nonmetal composite coating described in the first aspect, wherein the Me1X layer is deposited by magnetron sputtering or cathodic arc evaporation, the Me2 layer is deposited by bipolar high-power pulsed magnetron sputtering, and the Me1X layer and the Me2 layer are deposited alternately to form the metal-nonmetal composite coating.
[0016] The deposition target for the Me1X layer is at least one; the deposition target for the Me2 layer is at least two, and can be an even number, and can be a rectangular or circular planar structure or a cylindrical structure.
[0017] In some preferred embodiments, the forward peak current density deposited by the bipolar high-power pulsed magnetron sputtering method is 0.1~0.5 A / cm². 2 The peak current density is calculated by dividing the peak current by the working surface area of the target material.
[0018] In some preferred embodiments, the discharge time for sputtering deposition by the bipolar high-power pulsed magnetron sputtering method is 10~100μs.
[0019] In some preferred embodiments, the charging time is 50~1000μs.
[0020] In some preferred embodiments, the average power density of the sputtered deposition by the bipolar high-power pulsed magnetron sputtering method is less than or equal to 30 W / cm². 2 The average power density is calculated by dividing the average power by the working surface area of the target material.
[0021] In some preferred embodiments, the workpiece's revolution speed is 0~10 rpm during the deposition of the metal-nonmetal composite coating; In some preferred embodiments, the substrate bias voltage during the deposition of the metal-nonmetal composite coating is 0 to -500V; In some preferred embodiments, the deposition temperature of the metal-nonmetal composite coating is 20~500°C.
[0022] A third aspect of the present invention is to provide an application of the metal-nonmetal composite coating described in the first aspect as a protective coating or reinforcing coating on the surface of a metal material.
[0023] The metallic materials include pure metals and metal alloys, such as titanium alloys and cutting tools.
[0024] The beneficial effects of this invention are: (1) The present invention provides a metal-nonmetal composite coating having a multilayer structure, the hardness and toughness of which do not decrease significantly with the increase of the thickness or number of metal layers, and can maintain a high level of hardness and toughness even with a high metal layer thickness or number of layers, greatly expanding the process window of nano multilayer / superlattice coating.
[0025] (2) The present invention also provides a method for preparing the metal-nonmetal composite coating, by introducing a bipolar high-power pulsed magnetron sputtering method, by optimizing the conditions to improve the ionization rate of the metal and the incident substrate ion energy, by using strong ion energy bombardment to achieve strong interfacial strain and interfacial mixing at the interlayer interface of the nano-multilayer coating, thereby enhancing the interfacial bonding between the coating and the substrate, while improving the density, and finally maintaining the high hardness and toughness of the nano-multilayer coating.
[0026] (3) The present invention also provides an application of the metal-nonmetal composite coating, which, based on the high hardness and high toughness of the metal-nonmetal composite coating in a wide process window, can be used as a protective coating or reinforcing coating for the surface of metal materials in extreme service environments such as cutting tools or aerospace vehicles. Attached Figure Description
[0027] Figure 1 This is a schematic diagram illustrating the principle of selective acceleration of incident ions using BP-HiPIMS technology. Figure 2 The diagram shows the cathode current and voltage waveforms during BP-HiPIMS sputtering of the W target in Example 4. Figure 3 The diagram shows the cathode current and voltage waveforms during BP-HiPIMS sputtering of the W target in Example 5. Figure 4 The diagram shows the cathode current and voltage waveforms during BP-HiPIMS sputtering of the W target in Example 6. Figure 5 The diagram shows the cathode current and voltage waveforms during BP-HiPIMS sputtering of the Mo target in Example 8. Figure 6 The diagram shows the cathode current and voltage waveforms during BP-HiPIMS sputtering of the Mo target in Example 9. Figure 7 Line graphs showing the hardness, elastic modulus, and residual stress of the coatings obtained in Examples 1-6; Figure 8 The hardness / elastic modulus (H / E) and hardness of the coatings deposited in Examples 1-6 are shown. 3 Elastic modulus 2 (H) 3 / E 2 Line chart; Figure 9 The images show the Vickers indentation morphology of the coatings obtained in Examples 1-6 under a load of 10N using SEM. Figure 10 The images show SEM images of the Vickers indentation morphology of the coatings obtained in Examples 1-6 under a load of 20 N. Figure 11 This is a cross-sectional topography of the coating obtained by deposition in Example 1; Figure 12 This is a cross-sectional topography of the coating obtained by deposition in Example 2; Figure 13 This is a cross-sectional morphology diagram of the coating obtained by deposition in Example 3; Figure 14 This is a cross-sectional morphology diagram of the coating obtained by deposition in Example 4; Figure 15 This is a cross-sectional morphology diagram of the coating obtained by deposition in Example 5; Figure 16 This is a cross-sectional morphology diagram of the coating obtained by deposition in Example 6; Figure 17 This is a transmission electron microscope (TEM) image of the coating obtained by deposition in Example 4; Figure 18 The waveforms of hardness and elastic modulus of the coatings obtained by deposition in Examples 7-9 are shown. Figure 19 The hardness / elastic modulus (H / E) and hardness of the coatings deposited in Examples 7-9 are shown. 3 Elastic modulus 2 (H) 3 / E 2 Line chart; Figure 20 This is a cross-sectional topography of the coating obtained by deposition in Example 7; Figure 21 This is a cross-sectional morphology diagram of the coating obtained by deposition in Example 8; Figure 22 This is a cross-sectional morphology diagram of the coating obtained by deposition in Example 9. Detailed Implementation
[0028] The present invention will be further described in detail below through specific embodiments.
[0029] Unless otherwise specified, the raw materials, reagents, or apparatus used in the following examples and comparative examples are all available from conventional commercial sources or can be obtained by existing technical methods. Unless otherwise specified, the test or experimental methods are conventional methods in the art.
[0030] Unless otherwise specified, the term "about" in this invention actually means that the error is allowed to be within ±2%, for example, about 100 is actually 100 ± 2% × 100.
[0031] The embodiments of the present invention relate to a high-hardness TiB2 / W multilayer coating that can be used in cutting tools, comprising alternating layers of TiB2 and W, wherein the thickness of a single TiB2 layer is less than 100 nm, the total thickness of the TiB2 layer is 1.5 μm, the thickness of a single W layer is less than 100 nm, the total thickness of the W layer is 1.94~3.5 μm, and the total thickness of the multilayer coating is 3.44~5.02 μm. The preparation method includes the following steps: In an Ar atmosphere, alternating deposition was performed using two W targets and one TiB2 target. BP-HiPIMS was connected to the two W targets, which acted as anode and cathode to each other. One W target underwent glow discharge during the negative pulse application time, while the other W target bombarded the substrate during the positive pulse application time. The working peak current of the BP-HiPIMS discharge target surface was 54~124A in the forward direction and 22~104A in the reverse direction. The target surface size was 100×500mm. The discharge time of BP-HiPIMS was 10~100μs, the charging time was 50~500μs, and the W target power was 3~6kW. The TiB2 target was connected to the dcMS power supply with a power of 3kW. The rotating speed was 1rpm, the substrate bias voltage was -100~-500V, the deposition time of the multilayer coating was 3h, and the deposition temperature was 400℃.
[0032] Embodiments of the present invention also relate to a wear-resistant, corrosion-resistant, and high-temperature-resistant TiAlN / MoN multilayer coating, which can be widely used in the aerospace field to meet the requirements of wear resistance, corrosion resistance, and high-temperature resistance under extreme service environments. This multilayer coating consists of alternating layers of TiAlN and MoN, and its preparation method includes the following steps: In a pure N2 atmosphere, two Mo targets and one TiAl target were used for alternating deposition. BP-HiPIMS was connected to two Mo targets, which acted as anode and cathode to each other. One Mo target underwent glow discharge during the negative pulse application time, while the other Mo target bombarded the substrate during the positive pulse application time. The working peak current of the BP-HiPIMS discharge target surface was 24~36A in the forward direction and 90~204A in the reverse direction. The discharge time of BP-HiPIMS was 70μs, the charging time was 100μs, and the target power was 2~4kW. The TiAl target was connected to a dcMS power supply with a power of 6kW. The rotating frame speed was 1rpm, the substrate bias voltage was -100V, the deposition time of the multilayer coating was 3h, and the deposition temperature was 400℃.
[0033] Example 1 This embodiment relates to a TiB2 coating with a thickness of 2.5 μm, and its preparation method includes the following steps: (1) Substrate treatment: The surface of the substrate to be sputtered is sputtered and cleaned by glow discharge etching. Specifically, a mechanical pump is started to roughly pump the deposition chamber. After the chamber pressure is lower than 20 Pa, a molecular pump is started to perform high-vacuum evacuation. The molecular pump is used to pump the chamber pressure until it is lower than 3.0 × 10⁻⁶ Pa. -2 After Pa, start the heating system. When the vacuum chamber reaches the background vacuum level of 1.0 × 10⁻⁶, continue heating until the vacuum chamber reaches the background vacuum level of 1.0 × 10⁻⁶. -2 After Pa, argon gas is introduced and the ion source is turned on to etch and clean the substrate.
[0034] The etching process parameters are as follows: ion source current 10A, substrate bias voltage 200V, argon flow rate 300sccm, working pressure maintained at approximately 0.4Pa, and etching time 40min.
[0035] (2) Coating sputtering: A TiB2 monolayer coating was deposited on the etched and cleaned substrate by DC magnetron sputtering (dcMS). The deposition chamber pressure was 0.4 Pa, the TiB2 target power was 2 kW, the TiB2 monolayer deposition time was 1800 s, the substrate rotation speed was 1 rpm, the substrate bias voltage of the TiB2 monolayer coating was -100 V, and the deposition temperature was 400 °C.
[0036] Example 2 This embodiment relates to a TiB2 coating with a thickness of 670 nm. The difference in its preparation method compared to Example 1 is that it is formed using HiPIMS sputtering, specifically including the following steps: (1) Substrate treatment: The surface of the substrate to be sputtered is sputtered and cleaned by glow discharge etching. Specifically, a mechanical pump is started to roughly pump the deposition chamber. After the chamber pressure is lower than 20 Pa, a molecular pump is started to perform high-vacuum evacuation. The molecular pump is used to pump the chamber pressure until it is lower than 3.0 × 10⁻⁶ Pa. -2 After Pa, start the heating system. When the vacuum chamber reaches the background vacuum level of 1.0 × 10⁻⁶, continue heating until the vacuum chamber reaches the background vacuum level of 1.0 × 10⁻⁶. -2 After Pa, argon gas is introduced and the ion source is turned on to etch and clean the substrate.
[0037] The etching process parameters are as follows: ion source current 10A, substrate bias voltage 200V, argon flow rate 300sccm, working pressure maintained at approximately 0.4Pa, and etching time 40min.
[0038] (2) Coating sputtering: A TiB2 monolayer coating was deposited on the etched and cleaned substrate using high-power pulsed magnetron sputtering (HiPIMS). The chamber pressure was 0.25 Pa, the TiB2 target discharge power was 2.5 kW, the peak current was 384 A, and the peak current density was 0.77 A / cm³. 2 The pulse width was 30 μm, the frequency was 600 Hz, the substrate rotation speed was 1 rpm, the substrate bias voltage was -100 V, the TiB2 monolayer deposition time was 4 h, and the deposition temperature was 400 ℃.
[0039] Example 3 This embodiment relates to a W coating with a thickness of 1.53 μm, and its preparation method includes the following steps: (1) Substrate treatment: The surface of the substrate to be sputtered is sputtered and cleaned by glow discharge etching. Specifically, a mechanical pump is started to roughly pump the deposition chamber. After the chamber pressure is lower than 20 Pa, a molecular pump is started to perform high-vacuum evacuation. The molecular pump is used to pump the chamber pressure until it is lower than 3.0 × 10⁻⁶ Pa. -2 After Pa, start the heating system. When the vacuum chamber reaches the background vacuum level of 1.0 × 10⁻⁶, continue heating until the vacuum chamber reaches the background vacuum level of 1.0 × 10⁻⁶. -2 After Pa, argon gas is introduced and the ion source is turned on to etch and clean the substrate.
[0040] The etching process parameters are as follows: ion source current 10A, substrate bias voltage 200V, argon flow rate 300sccm, working pressure maintained at approximately 0.4Pa, and etching time 40min.
[0041] (2) Coating sputtering: A single layer of W coating was deposited on the etched and cleaned substrate by bipolar high-power pulsed magnetron sputtering (BP-HiPIMS). The working peak current of the W target surface was 96A and the peak current of the reverse side was 60A. The target surface size was 100×500mm. The positive electrode switching discharge time of BP-HiPIMS was 60μs and the charging time was 100μs. The negative electrode switching discharge time was 60μs and the charging time was 100μs. The W target power was 6kW. The substrate rotation speed was 1rpm. The substrate bias voltage was -200V. The deposition time of the single layer of W coating was 3h and the deposition temperature was 400℃.
[0042] Example 4 This embodiment relates to a TiB2 / W nanolayered coating with a total coating thickness of 3.73 μm, a TiB2 monolayer thickness of 3.7 nm, and a W monolayer thickness of 17 nm. The preparation method includes the following steps: (1) Substrate treatment: The surface of the substrate to be sputtered is sputtered and cleaned by glow discharge etching. Specifically, a mechanical pump is started to roughly pump the deposition chamber. After the chamber pressure is lower than 20 Pa, a molecular pump is started to perform high-vacuum evacuation. The molecular pump is used to pump the chamber pressure until it is lower than 3.0 × 10⁻⁶ Pa. -2 After Pa, start the heating system. When the vacuum chamber reaches the background vacuum level of 1.0 × 10⁻⁶, continue heating until the vacuum chamber reaches the background vacuum level of 1.0 × 10⁻⁶. -2 After Pa, argon gas is introduced and the ion source is turned on to etch and clean the substrate.
[0043] The etching process parameters are as follows: ion source current 10A, substrate bias voltage 200V, argon flow rate 300sccm, working pressure maintained at approximately 0.4Pa, and etching time 40min.
[0044] (2) Coating sputtering: The TiB2 layer was deposited by DC magnetron sputtering (dcMS), and the W layer was deposited by bipolar high-power pulsed magnetron sputtering (BP-HiPIMS). The TiB2 target was connected to the dcMS power supply with a target power of 3kW, the substrate rotation speed was 1rpm, and the substrate bias voltage was -100V. The W target was connected to the BP-HiPIMS power supply with a target surface working forward peak current of 54A and a reverse peak current of 22A. The target surface size was 100×500mm. The positive electrode switching discharge time was 60μs and the charging time was 100μs. The negative electrode switching discharge time was 60μs and the charging time was 100μs. The W target power was 3kW.
[0045] The layers are deposited in the order of "W layer-TiB2 layer-W layer", with a total of 180 "W layer-TiB2 layer-W layer" and a total of 540 layers, forming a TiB2 / W stacked structure. Since the W layer consists of two deposited layers, its single-layer thickness in the stacked structure is slightly larger than that of the TiB2 layer.
[0046] The total deposition time was 3 hours, the deposition temperature was 400℃, the atmosphere was pure Ar, and the chamber pressure was 0.4 Pa.
[0047] The cathode current and voltage waveforms for this embodiment using BP-HiPIMS sputtering of the W target are shown in the appendix. Figure 2 .
[0048] Example 5 This embodiment relates to a TiB2 / W nanolayered coating with a total coating thickness of 4.56 μm, a TiB2 monolayer thickness of 3.7 nm, and a W monolayer thickness of 21 nm. The preparation method includes the following steps: (1) Substrate treatment: The surface of the substrate to be sputtered is sputtered and cleaned by glow discharge etching. Specifically, a mechanical pump is started to roughly pump the deposition chamber. After the chamber pressure is lower than 20 Pa, a molecular pump is started to perform high-vacuum evacuation. The molecular pump is used to pump the chamber pressure until it is lower than 3.0 × 10⁻⁶ Pa. -2 After Pa, start the heating system. When the vacuum chamber reaches the background vacuum level of 1.0 × 10⁻⁶, continue heating until the vacuum chamber reaches the background vacuum level of 1.0 × 10⁻⁶. -2 After Pa, argon gas is introduced and the ion source is turned on to etch and clean the substrate.
[0049] The etching process parameters are as follows: ion source current 10A, substrate bias voltage 200V, argon flow rate 300sccm, working pressure maintained at approximately 0.4Pa, and etching time 40min.
[0050] (2) Coating sputtering: The TiB2 layer was deposited by DC magnetron sputtering (dcMS), and the W layer was deposited by bipolar high-power pulsed magnetron sputtering (BP-HiPIMS). The TiB2 target was connected to the dcMS power supply with a target power of 3kW, the substrate rotation speed was 1rpm, and the substrate bias voltage was -200V. The W target was connected to the BP-HiPIMS power supply with a target surface working forward peak current of 96A and a reverse peak current of 60A. The target surface size was 100×500mm. The positive electrode switching discharge time was 60μs and the charging time was 100μs. The negative electrode switching discharge time was 60μs and the charging time was 100μs. The W target power was 6kW.
[0051] The layers were stacked in the order of "W layer-TiB2 layer-W layer", with a total of 180 "W layer-TiB2 layer-W layer" stacks and a total of 540 layers.
[0052] The total deposition time was 3 hours, the deposition temperature was 400℃, the atmosphere was pure Ar, and the chamber pressure was 0.4 Pa.
[0053] The cathode current and voltage waveforms for this embodiment using BP-HiPIMS sputtering of the W target are shown in the appendix. Figure 3 .
[0054] Example 6 This embodiment relates to a TiB2 / W nanolayered coating with a total coating thickness of 3.65 μm, a TiB2 monolayer thickness of 3.7 nm, and a W monolayer thickness of 16.5 nm. The preparation method includes the following steps: (1) Substrate treatment: The surface of the substrate to be sputtered is sputtered and cleaned by glow discharge etching. Specifically, a mechanical pump is started to roughly pump the deposition chamber. After the chamber pressure is lower than 20 Pa, a molecular pump is started to perform high-vacuum evacuation. The molecular pump is used to pump the chamber pressure until it is lower than 3.0 × 10⁻⁶ Pa. -2 After Pa, start the heating system. When the vacuum chamber reaches the background vacuum level of 1.0 × 10⁻⁶, continue heating until the vacuum chamber reaches the background vacuum level of 1.0 × 10⁻⁶. -2 After Pa, argon gas is introduced and the ion source is turned on to etch and clean the substrate.
[0055] The etching process parameters are as follows: ion source current 10A, substrate bias voltage 200V, argon flow rate 300sccm, working pressure maintained at approximately 0.4Pa, and etching time 40min.
[0056] (2) Coating sputtering: The TiB2 layer was deposited by DC magnetron sputtering (dcMS), and the W layer was deposited by bipolar high-power pulsed magnetron sputtering (BP-HiPIMS). The TiB2 target was connected to the dcMS power supply with a target power of 3kW, the substrate rotation speed was 1rpm, and the substrate bias voltage was -500V. The W target was connected to the BP-HiPIMS power supply with a target surface working forward peak current of 124A and a reverse peak current of 104A. The target surface size was 100×500mm. The positive electrode switching discharge time was 30μs and the charging time was 130μs. The negative electrode switching discharge time was 30μs and the charging time was 130μs. The W target power was 6kW.
[0057] The layers were stacked in the order of "W layer-TiB2 layer-W layer", with a total of 180 "W layer-TiB2 layer-W layer" stacks and a total of 540 layers.
[0058] The total deposition time was 3 hours, the deposition temperature was 400℃, the atmosphere was pure Ar, and the chamber pressure was 0.4 Pa.
[0059] The cathode current and voltage waveforms for this embodiment using BP-HiPIMS sputtering of the W target are shown in the appendix. Figure 4 .
[0060] Example 7 This embodiment relates to a TiAlN coating, the preparation method of which includes the following steps: (1) Substrate treatment: The surface of the substrate to be sputtered is sputtered and cleaned by glow discharge etching. Specifically, a mechanical pump is started to roughly pump the deposition chamber. After the chamber pressure is lower than 20 Pa, a molecular pump is started to perform high-vacuum evacuation. The molecular pump is used to pump the chamber pressure until it is lower than 3.0 × 10⁻⁶ Pa. -2 After Pa, start the heating system. When the vacuum chamber reaches the background vacuum level of 1.0 × 10⁻⁶, continue heating until the vacuum chamber reaches the background vacuum level of 1.0 × 10⁻⁶. -2 After Pa, argon gas is introduced and the ion source is turned on to etch and clean the substrate.
[0061] The etching process parameters are as follows: ion source current 10A, substrate bias voltage 200V, argon flow rate 300sccm, working pressure maintained at approximately 0.4Pa, and etching time 40min.
[0062] (2) Coating sputtering: A TiAlN monolayer coating was deposited on the etched and cleaned substrate by DC magnetron sputtering (dcMS). The deposition chamber pressure was 0.4 Pa, the TiAl target power was 6 kW, the TiAlN monolayer deposition time was 3 h, the substrate rotation speed was 1 rpm, the substrate bias voltage was -100 V, the deposition temperature was 400 °C, the atmosphere was pure N2, and the chamber pressure was 0.5 Pa.
[0063] Example 8 This embodiment relates to a TiAlN / MoN nanolayered coating, the preparation method of which includes the following steps: (1) Substrate treatment: The surface of the substrate to be sputtered is sputtered and cleaned by glow discharge etching. Specifically, a mechanical pump is started to roughly pump the deposition chamber. After the chamber pressure is lower than 20 Pa, a molecular pump is started to perform high-vacuum evacuation. The molecular pump is used to pump the chamber pressure until it is lower than 3.0 × 10⁻⁶ Pa. -2 After Pa, start the heating system. When the vacuum chamber reaches the background vacuum level of 1.0 × 10⁻⁶, continue heating until the vacuum chamber reaches the background vacuum level of 1.0 × 10⁻⁶. -2 After Pa, argon gas is introduced and the ion source is turned on to etch and clean the substrate.
[0064] The etching process parameters are as follows: ion source current 10A, substrate bias voltage 200V, argon flow rate 300sccm, working pressure maintained at approximately 0.4Pa, and etching time 40min.
[0065] (2) Coating sputtering: TiAlN layer was deposited by DC magnetron sputtering (dcMS), and MoN layer was deposited by bipolar high-power pulsed magnetron sputtering (BP-HiPIMS). TiAl target was connected to dcMS power supply, TiAl target power was 6kW, substrate rotation speed was 1rpm, and substrate bias voltage was -100V; Mo target was connected to BP-HiPIMS power supply, Mo target surface working forward peak current was 32A, reverse peak current was 200A, positive electrode switching discharge time was 70μs, charging time was 100μs, negative electrode switching discharge time was 70μs, charging time was 1000μs, and Mo target power was 4kW.
[0066] The total deposition time was 3 hours, the deposition temperature was 400℃, the atmosphere was pure N2, and the chamber pressure was 0.5 Pa.
[0067] The cathode current and voltage waveforms for Mo sputtering using a BP-HiPIMS target in this embodiment are shown in the appendix. Figure 5 .
[0068] Example 9 This embodiment relates to a TiAlN / MoN nanolayered coating, the preparation method of which includes the following steps: (1) Substrate treatment: The surface of the substrate to be sputtered is sputtered and cleaned by glow discharge etching. Specifically, a mechanical pump is started to roughly pump the deposition chamber. After the chamber pressure is lower than 20 Pa, a molecular pump is started to perform high-vacuum evacuation. The molecular pump is used to pump the chamber pressure until it is lower than 3.0 × 10⁻⁶ Pa. -2 After Pa, start the heating system. When the vacuum chamber reaches the background vacuum level of 1.0 × 10⁻⁶, continue heating until the vacuum chamber reaches the background vacuum level of 1.0 × 10⁻⁶. -2 After Pa, argon gas is introduced and the ion source is turned on to etch and clean the substrate.
[0069] The etching process parameters are as follows: ion source current 10A, substrate bias voltage 200V, argon flow rate 300sccm, working pressure maintained at approximately 0.4Pa, and etching time 40min.
[0070] (2) Coating sputtering: TiAlN layer was deposited by DC magnetron sputtering (dcMS), and MoN layer was deposited by bipolar high-power pulsed magnetron sputtering (BP-HiPIMS). TiAl target was connected to dcMS power supply, TiAl target power was 6kW, substrate rotation speed was 1rpm, and substrate bias voltage was -100V; Mo target was connected to BP-HiPIMS power supply, Mo target surface working forward peak current was 24A, reverse peak current was 90A, positive electrode switching discharge time was 70μs, charging time was 100μs, negative electrode switching discharge time was 70μs, charging time was 1000μs, and Mo target power was 2kW.
[0071] The total deposition time was 3 hours, the deposition temperature was 400℃, the atmosphere was pure N2, and the chamber pressure was 0.5 Pa.
[0072] The cathode current and voltage waveforms for Mo sputtering using a BP-HiPIMS target in this embodiment are shown in the appendix. Figure 6 .
[0073] The hardness, elastic modulus, and residual stress of the coatings deposited in Examples 1-6 were tested. A nanoindenter was used to test the hardness and elastic modulus of the deposited coatings, and a stress meter was used to test the residual stress of the deposited coatings. The test results are shown in the appendix. Figure 7-8 According to the appendix Figure 7-8 The results showed that the hardness, elastic modulus, residual stress, hardness / elastic modulus (H / E), and hardness of the TiB2 / W nanolayered coatings in Examples 4-6 were... 3 Elastic modulus 2 (H) 3 / E 2 The ratios of the two materials were relatively close, and their hardness remained around 30 GPa. In comparison, the TiB2 monolayer coating prepared by HiPIMS showed the best hardness, followed by the TiB2 monolayer coating prepared by dcMS, both reaching over 30 GPa. The hardness of the pure W monolayer coating prepared by BP-HiPIMS was only 12 GPa.
[0074] Indentation tests were performed on the coatings obtained in Examples 1-6. SEM images of the Vickers indentation morphology of each coating under loads of 10N and 20N are attached. Figure 9-10The TiB2 monolayer coating prepared by HiPIMS exhibited the highest number of radial cracks under a 10N load, and was crushed under a 20N load. The TiB2 / W nanolayer coatings all demonstrated excellent indentation toughness, with no radial cracks observed and far fewer circumferential cracks compared to the TiB2 monolayer coating prepared by HiPIMS. The pure W monolayer coating prepared by BP-HiPIMS, due to its lower hardness, showed primarily plastic extrusion deformation during indentation, without crack initiation.
[0075] Cross-sectional morphology diagrams of the coatings obtained by deposition in Examples 1-6 are attached. Figure 11-16 The transmission electron microscope image of the coating obtained by deposition in Example 4 is attached. Figure 17 According to the appendix Figure 17 The TiB2 / W nanolayered structure prepared in this embodiment has a distinct layered stacking structure and clearly distinguishable interlayer interfaces.
[0076] The hardness and elastic modulus of the coatings deposited in Examples 7-9 were tested, and the test results are shown in the appendix. Figure 18-19 According to the appendix Figure 18-19 The results showed that the hardness, elastic modulus, H / E and H of the TiAlN / MoN nanolayered coating were... 3 / E 2 The ratios are all superior to those of TiAlN single-layer coatings.
[0077] Cross-sectional morphology diagrams of the coatings obtained by deposition in Examples 7-9 are attached. Figure 20-22 According to the appendix Figure 20-22 In Example 7, the columnar crystals of the deposited coating are coarse, while in Examples 8-9, the columnar crystals of the deposited coating are finer and the structure is more compact.
[0078] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.
Claims
1. A metal-nonmetal composite coating, characterized in that, comprises alternately stacked Me1X layers and Me2 layers; Me1 and Me2 are each independently selected from at least one of Ti, Al, Cr, Zr, Hf, W, Mo, Ta, Sc, Ni and V; Me1X is a boride, carbide, nitride or oxide of the metal Me1; At least part of the metal Me2 in the Me2 layer forms Me2X with X in the Me1X layer; The number of layers of each of the Me1X layers and the Me2 layers is greater than or equal to 3.
2. The metal-nonmetal composite coating according to claim 1, characterized in that, In the metal-nonmetal composite coating, the Me1X layer comprises TiB2 and the Me2 layer comprises W; or, the Me1X layer comprises TiAlN and the Me2 layer comprises Mo.
3. The metal-nonmetal composite coating according to claim 1, characterized in that, The thickness d1 of the Me1X layer satisfies 0<d1≤100nm; and / or, the thickness d2 of the Me2 layer satisfies 0<d2≤100nm.
4. The metal-nonmetal composite coating according to claim 1, characterized in that, The thickness of the metal-nonmetal composite coating is 0.5~10μm.
5. The method for preparing the metal-nonmetal composite coating according to any one of claims 1-4, characterized in that, The Me1X layer is deposited by magnetron sputtering or cathodic arc evaporation, and the Me2 layer is deposited by sputtering using a bipolar high-power pulsed magnetron sputtering method, and the two are alternately deposited to form the metal-nonmetal composite coating.
6. The preparation method according to claim 5, characterized in that, The forward peak current density deposited by the bipolar high-power pulsed magnetron sputtering method is 0.1~0.5 A / cm³. 2 .
7. The preparation method according to claim 5, characterized in that, The discharge time of the bipolar high-power pulsed magnetron sputtering method for sputter deposition is 10~100μs; and / or, the charging time is 50~1000μs.
8. The preparation method according to claim 5, characterized in that, The average power density deposited by the bipolar high-power pulsed magnetron sputtering method is less than or equal to 30 W / cm³. 2 .
9. The preparation method according to claim 5, characterized in that, comprises one or more of the following features: The revolution speed of the workpiece during deposition is 0~10rpm; The substrate bias during deposition is 0~-500V; The deposition temperature is 20~500℃.
10. Use of the metal-nonmetal composite coating according to any one of claims 1 to 4 or the metal-nonmetal composite coating prepared by the preparation method according to any one of claims 5 to 9 as a protective coating or a strengthening coating on the surface of a metal material.